A novel mechanical design of disc brakes for fault diagnosis and monitoring positive braking pressure in mine hoist. (April 2019) - Xu, Guiyun; Song, Di; Zhang, Di; Zhang, Xiaoguang; Sha, Shikang
As the final executor of the braking system of coal mine hoists, the disc brake directly affects the safety and reliability of mine hoists. Aimed to the problem of failure of hoist disc brake, according to its structural characteristics and functional requirements, this article proposes a disc brake that monitors positive brake pressure in real time and has a certain brake fault diagnosis function and develops a prototype. Based on SolidWorks, its virtual prototype model is established, and its finite element model is established by ANSYS Workbench. The static and dynamic simulations are performed on the entire disc brake and key components to obtain overall vibration characteristics and mechanical characteristics. Prototypes of disc brake and sensors are machined to perform test experiments to measure the performance, and experimental data are analyzed in conjunction with theories. The experimental results show that the disc brake can realize real-time effective monitoring of the positive brake pressure. It has the function of fault diagnosis, and its strength and stiffness meet the requirements with lower cost. The correctness and effectiveness of the proposed structure scheme are verified.